2014
DOI: 10.1142/s0219635214500253
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of acute restraint stress in male albino rats and the impact of pretreatment with quetiapine versus ghrelin

Abstract: Stress is any condition that seriously affects the balance of the organism physiologically and psychologically. Stress activates the hypothalamic-pituitary-adrenal (HPA) releasing glucocorticoid hormones that produce generalized effects on different body systems including the nervous system. This study aimed to investigate the effect of acute restraint stress (ARS) on cognitive performance by measuring spatial working memory in Y-maze, behavior (anxiety and exploratory behavior) in open field test, expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…We sought to investigate the association between prenatal stress and anxiety-related behaviors in another popular paradigm. While the Open Field is regularly used for anxiety assessments (Amin et al, 2014), the data collected after the test vary from one study to another. Some research teams examined the crossover, rearing, head poke and corner activities (Pohorecky & Roberts, 1991) while others preferred to take into account the percent (Hougaard et al, 2005) or the total time spent in the center (Laloux et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…We sought to investigate the association between prenatal stress and anxiety-related behaviors in another popular paradigm. While the Open Field is regularly used for anxiety assessments (Amin et al, 2014), the data collected after the test vary from one study to another. Some research teams examined the crossover, rearing, head poke and corner activities (Pohorecky & Roberts, 1991) while others preferred to take into account the percent (Hougaard et al, 2005) or the total time spent in the center (Laloux et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The hippocampus is necessary for the formation of declarative memory in humans, spatial memory in rodents, memory consolidation, reconsolidation, long-term memory persistence, novelty detection, habituation, and long-term potentiation [2]. ARS adversely affects the hippocampus both structurally and functionally [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that QUE transiently disrupts avoidance behavior in a conditioned avoidance response task because it only transiently blocks D 2 receptors [44]. It has also been reported that QUE decreases object recognition deficits in a rat model of malformations of cortical development [26], stress-induced spatial working memory impairment [45], and reverses methamphetamine-induced cognitive deficits [46]. The benefits attributed to QUE could be due, in part to, to increased levels of DA in the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%